Evaluating the Psychometric Properties of the Migraine Functional Impact Questionnaire (MFIQ) - Kawata, Ariane K.; Hareendran, Asha; Shaffer, Shannon; Mannix, Sally; Thach, Andrew; Desai, Pooja; Mikol, Daniel D.; Ortmeier, Brian; Bayliss, Martha; Buse, Dawn C. (Headache, 2019)
Background Migraine is a chronic neurologic disease that can be associated with significant migraine‐related impact, disability, and burden. Patient‐reported outcome measures (PRO) are included in clinical trials of migraine interventions to capture treatment effects from a patient perspective. Clinical and regulatory guidelines also encourage use of PROs in trials. The Migraine Functional Impact Questionnaire (MFIQ) is a novel PRO measure, assessing the impact of migraine on Physical Function (PF), Usual Activities (UA), Social Function (SF), and Emotional Function (EF), in the past 7 days. Scientific methods recommended to meet the requirements of the U.S. Food and Drug Administration were followed, to ensure that the MFIQ content included outcomes that were relevant to adults with migraine and were clinically relevant, specifically to evaluate preventive treatments for migraine. Objective The objective of this study was to conduct item analyses informing item reduction and scoring, and to evaluate the psychometric properties of the MFIQ. Methods In a prospective, observational study, adults with migraine completed the MFIQ as well as additional clinical and PRO instruments, including the Headache Impact Test (HIT‐6TM), Patient‐Reported Outcomes Measurement Information System Physical Function Short Form 10a (PROMIS‐PF), Migraine‐Specific Quality‐of‐Life Questionnaire (MSQ), and Patient Global Rating of Change (PGIC). Item‐level evaluation, item response theory (IRT), and factor analysis were used to select final MFIQ items, identify domains, and inform scoring. Psychometric properties of the MFIQ were evaluated to assess reliability (internal consistency and test–retest), validity (construct and known‐groups), and responsiveness. Results The study enrolled 569 adults with migraine. Subjects had an average age of 39.9 years (SD 12.0), 87.2% were female, and 80.8% were white. Five items were dropped from the draft version based on results of item‐level analyses reviewed in the context of previous qualitative research to produce the final 26‐item MFIQ (v.2). Four domain scores (PF, UA, SF, and EF) and a global item score for impact on UA were identified. Higher scores on a 0‐100 scale represent greater impact. All scores exhibited high internal consistency (α ≥ 0.89) and moderate test–retest reliability among stable subjects (ICCs ≥ 0.47). Construct validity was demonstrated by significant correlations (all P < .0001) between MFIQ domain scores, related PRO scores, and the frequency of migraine days and headache days. All domain scores differentiated between subgroups (“known groups”) defined based on established levels of clinical severity: number of monthly migraine and headache days, migraine interference levels and scores on other PRO instruments (P < .05). Improvements in MFIQ scores corresponded with clinical improvement (percent reduction in monthly migraine days), improvement in migraine interference with daily activities, and related improvements in PRO scores (P < .05), demonstrating that the MFIQ was responsive to changes in migraine impact. Conclusions The MFIQ is a reliable and valid measure that can be used to collect data about migraine impact. The MFIQ is being used to evaluate outcomes of migraine interventions in clinical trials and observational studies. It could potentially also be used in clinical practice both for initial and ongoing assessments for monitoring outcomes and to enhance communication between patients and healthcare professionals for the management of migraine.